Integration von Fährfahrplänen in co-modale Autorouten- und Reiseplaner. - Just, Ulrich; Kröpel, Stefan; Schwartz, Thomas (Deutscher Verkehrs-Verl., 2008)
Internet-Autoroutenplaner bieten bei Fährverbindungen kaum Informationen für die Reiseplanung. Bislang gab es kein Datenpool mit Fährfahrplänen und Hafeninformationen. Daher wurde die Initiative zum Aufbau eines Fährdatenpools und zur Entwicklung eines Auto- und Fährroutenplaners von den entsprechenden Ministerien und Straßenbaubehörden des euroregionalen Telematikprojekts VIKING ergriffen. Der Fährdatenpool - derzeit auf den Ostseeraum und Teile der Nordsee begrenzt - trägt zur Vernetzung der Verkehrsträger Straße, Schiene und Wasser bei. difu

In car route and travel planners in the Internet ferry timetables are not included. The main reason for this was the fact that there was no ferry data pool with ferry timetables and port information existing that service providers could derive data from. However, the ferry transport plays an important role between Scandinavia and Germany. It is therefore desirable to integrate valid timetables into the car route planner and timetable information systems. Since no other institution was willing to set up the ferry data pool and a combined car and ferry route planner for the Internet, the Transport Ministries and Road Administrations in VIKING started the project and set up the ferry data pool. The ferry data pool is supposed to contribute to a better connection of the transport modes road, rail and sea, a faster development of co-modal traveller information services on the trans-European road network (TERN) and offer service providers car route and travel planners an easy access to the ferry data. difu
Keywords: Verkehr; Individualverkehr; Autoverkehr; Informationstechnologie; Kommunikationstechnologie; Fähre; Fährverkehr; Hafen; Wasserverkehr; Brücke; EDV-Software; Routenplanung; Fährverbindung; Fahrplan; Verkehrsinformation; Vernetzung; Internet; Maut